PEMETAAN KUALITAS AIR TANAH DI DESA DAUH PURI KAJA KOTA DENPASAR - ABADI, M. FAIRUZ; MAHENDRA, M.S.; SUYASA, I.W BUDIARSA (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
Groundwater pollution has been an issue of concern for environmentalists. This study aims to detect the possibilities of municipal ground water quality deteriorations, to know how does the classification status of groundwater contamination, and also to map distribution of the status of groundwater contamination in Desa Dauh Puri Kaja Denpasar City. A method to assess municipal water quality is using Water Quality Index method, with the cluster classification. Mapping groundwater contamination is done using Arc View 3.3 (Geografic Information System) The parameters used are TSS, BOD, COD, NH3-N, Cd Cr (VI), Cl, N, Sulfate, H2S and total coliform. This research proves that groundwater quality status on a cluster two is in the category of heavy impurity, whereas in cluster two sources of pollutant in the material organic derived from water run off and seepage from rivers. Status of water quality in cluster three are on the same level with the water quality status in cluster one, but based on the characteristics of pollutants was found that the factor of pollutant in the cluster three caused sewage contamination of the active substance in detergent. in cluster one source pollutants is derived from organic waste (domestic waste). Suggestions and recommendations in this study aimed to the peoples concession of land in the Dauh Puri Kaja thats potentially affect for ground water quality should be equipped with sewage treatment plants (on-site sanitation), and to the government and related institutions in order to mobilize the potential of empowering community to create an environment with better quality, cleaner, more convenient to protect ground water.
Keywords: groundwater quality, municipal, mapping, geografic information system